2019
DOI: 10.1007/s13158-019-00252-5
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Agency: Opportunities and Constraints

Abstract: Children's agency accords with the principles emphasised by the Convention on the Rights of the Child (United Nations in Convention on the rights of the child. UN Office of High Commissioner for Human Rights (OHCHR), Geneva. Retrieved from, https ://www.ohchr .org/EN/Profe ssion alInt erest /Pages /CRC.aspx, 1989). This study focuses on children's opportunities for agency in first grade of a Finnish primary school. The research explored how children's agency was evident in photographs taken by 16 children on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Previous research has also suggested that adult educators play a dual role in creating the conditions for children's actions in institutional settings by affording the opportunities for action while maintaining the institutional order (Puroila et al 2012b;Sirkko et al 2019). Although the educators remained quite invisible in the storyline discussed here, they undoubtedly influence children's Fig.…”
Section: Building Places For Play Within Everyday Possibilities and Cmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous research has also suggested that adult educators play a dual role in creating the conditions for children's actions in institutional settings by affording the opportunities for action while maintaining the institutional order (Puroila et al 2012b;Sirkko et al 2019). Although the educators remained quite invisible in the storyline discussed here, they undoubtedly influence children's Fig.…”
Section: Building Places For Play Within Everyday Possibilities and Cmentioning
confidence: 81%
“…This is another reminder of the cultural and institutional practices that frame children's placebelonging, restricting their scope to build their own places. As previous research also noted, the rhythm of children's play in the preprimary school setting must adapt to the rhythm of everyday routines and practices (Juutinen & Viljamaa, 2016;Sirkko et al 2019).…”
Section: Building Places For Play Within Everyday Possibilities and Cmentioning
confidence: 88%
“…Houen et al 2016;James and James 2012;Mentha, Church, and Page 2015). Yet as Sirkko, Kyrönlampi, and Puroila (2019) point out, 'children's agency cannot be explored as an inner feature of individual children because ideas about children's agency are tightly connected to moral and political ideas about what kinds of agency are appropriate for children in specific cultural contexts. ' Houen et al (2016) suggest that teachers create spaces for children's agency.…”
Section: Editorialmentioning
confidence: 99%
“…Accordingly, there is an 'almost infinite list of definitions' (van Deth 2003: 170)" (Bettmer 2008: 213). In educational and childhood-related research contexts, definitions of children's participation usually refer to the UnCRC (e.g., Church & Bateman 2019) and/or are linked to concepts of (children's) agency (Baraldi 2014;Baraldi & Iervese 2014;Houen et al 2016;Prout 2000;James 2011;Sirkko et al 2019). The agency concept is based on findings from the field of childhood studies and recognizes children as "social actors" (Prout & James1990: 8).…”
Section: Theoretical and Empirical Underpinningsmentioning
confidence: 99%